New species of Acanthocinini from South America (Coleoptera: Cerambycidae) - Monné, Miguel A.; Monné, Marcela L. (Zootaxa, 2012)
New species of South American Acanthocinini are described: Neobaryssinus abbreviatus sp. nov. from French Guianaand Brazil (Amazonas); Baryssinus amoenus sp. nov. from French Guiana; Colobeutrypanus barclayi sp. nov. fromEcuador; Sporetus sticticus sp. nov. from Ecuador, French Guiana and Brazil (Pará); Oxathres simillima sp. nov. fromVenezuela; Oxathres griseostriata sp. nov. from Brazil (Maranhão) and Bolivia (Santa Cruz) and Oedopeza tavakiliani sp. nov. from French Guiana.